Nonskeletal and skeletal effects of high doses versus low doses of vitamin D3 in renal transplant recipients: Results of the VITALE (VITamin D supplementation in renAL transplant recipients) study, a randomized clinical trial - Marie Courbebaisse; Aurélie Bourmaud; Jean–Claude Souberbielle; Rébecca Sberro‐Soussan; Valérie Moal; Yannick Le Meur; Nassim Kamar; Laetitia Albano; Antoine Thierry; Jacques Dantal; Clément Danthu; Karine Moreau; et al. (2023)
Vitamin D sufficiency is associated with a reduced risk of fractures, diabetes mellitus, cardiovascular events, and cancers, which are frequent complications after renal transplantation. The VITALE (VITamin D supplementation in renAL transplant recipients) study is a multicenter double-blind randomized trial, including nondiabetic adult renal transplant recipients with serum 25-hydroxy vitamin D (25(OH) vitamin D) levels of <30 ng/mL, which is randomized 12 to 48 months after transplantation to receive high (100 000 IU) or low doses (12 000 IU) of cholecalciferol every 2 weeks for 2 months and then monthly for 22 months. The primary outcome was a composite endpoint, including diabetes mellitus, major cardiovascular events, cancer, and death. Of 536 inclusions (50.8 [13.7] years, 335 men), 269 and 267 inclusions were in the high-dose and low-dose groups, respectively. The serum 25(OH) vitamin D levels increased by 23 versus 6 ng/mL in the high-dose and low-dose groups, respectively (P < .0001). In the intent-to-treat analysis, 15% versus 16% of the patients in the high-dose and low-dose groups, respectively, experienced a first event of the composite endpoint (hazard ratio, 0.94 [0.60-1.48]; P = .78), whereas 1% and 4% of patients in the high-dose and low-dose groups, respectively, experienced an incident symptomatic fracture (odds ratio, 0.24 [0.07-0.86], P = .03). The incidence of adverse events was similar between the groups. After renal transplantation, high doses of cholecalciferol are safe but do not reduce extraskeletal complications (trial registration: ClinicalTrials.gov; identifier: NCT01431430).